Activation of Cofilin Increases Intestinal Permeability via Depolymerization of F-Actin During Hypoxia in vitro - Song, Huapei; Zhang, Jian; He, Wen; Wang, Pei; Wang, Fengjun (Frontiers in Physiology, 2019)
Mechanical barriers play a key role in maintaining the normal function of the intestinal mucosa. The barrier function of intestinal epithelial cells is significantly damaged after severe hypoxia. However, the molecular mechanisms underlying this hypoxia-induced damage are still not completely clear. Through the establishment of an in vitro cultured intestinal epithelial cell monolayer model (Caco-2), we treated cells with hypoxia or drugs (Jasplakinolide and Latrunculin A (LatA)) in order to detect changes in the transepithelial electrical resistance (TER), the expression of the cellular tight junction (TJ) proteins zonula occludens-1 (ZO-1) and occludin, the distribution of F-actin, the ratio of F-actin/G-actin content, and the expression of the cofilin protein. The results showed that hypoxia and drug treatment could both induce a significant reduction in the TER of the intestinal epithelial cell monolayer and a significant reduction in the expression of the ZO-1 and occludin protein. Hypoxia and LatA could cause a significant reduction in the ratio of F-actin/G-actin content, whereas Jasplakinolide caused a significant increase in the ratio of F-actin/G-actin content. After hypoxia, cofilin phosphorylation was decreased. We concluded that the barrier function of the intestinal epithelial cell monolayer was significantly damaged after severe burn injury. The molecular mechanism might be that hypoxia-induced F-actin depolymerization, and an imbalance between F-actin and G-actin through cofilin activation resulting in reduced expression and a change in the distribution of cellular TJ proteins.